A Pilot Study about Clinical Features of Aberrations Chromosome 22q - Emine Ikbal Atli (Georg Thieme Verlag KG, 2021)
Objective A significant number of genetic variations have been identified in chromosome 22, using molecular genetic techniques. Various genomic disorders on chromosome 22, including cat's eye syndrome caused by extra copies of the proximal region of the 22q chromosome, are now well-defined. Our aim in the study was to show phenotypic variability associated with rearrangements of the 22q chromosomal region. Methods We focused our study on clinical aspects of these disorders, including genetic testing, genotype-phenotype correlation, and potential treatments. A total of 998 patients were referred for genetic analysis (Karyotyping, MLPA, array-CGH) during January 2015 to February 2020 because of intellectual deficiency, behavior issues, and/or multiple congenital abnormalities in several genetics departments. Informed consent was obtained from all the patients and/or their parents. Results 22q11.21 or 22q13.33 microdeletions and 22q11.22-q11.23 microduplication were identified in 31 patients out of referrals. The 22q aberrations were detected in 31/998 patients, giving a prevalence of 3.1%. In this study, 18 patients with 22q11.2 (LCR22A-H) deletion, three patients with 22q13.31 deletion, 9 patients with 22q11.2 duplication and one patient with 22q13.31 duplication were identified. We report on the clinical and molecular characterization of 31 individuals with distal deletions and duplications of chromosome 22q. Conclusions The current study demonstrated in the largest postnatal case series reporting the whole spectrum of atypical phenotypic and genotypic variations at 22q. We believe that when all the phenotypic differences are taken into account, various anomalies including developmental delay and intellectual disability might be considered as an indication to search for aberrations of 22q along with congenital heart diseases.